2012
DOI: 10.4103/2230-8210.94256
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of the metabolic syndrome among newly diagnosed hypertensive patients

Abstract: Background:Cardiovascular disease risk factors have a tendency to cluster. The presence of such a cluster in an individual has been designated the metabolic syndrome (MetS). There is a paucity of reports of the prevalence of MetS in hypertensive patients in south east Nigeria. This study was undertaken to determine the prevalence of the metabolic syndrome (MetS) among newly diagnosed hypertensive patients using the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria in a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
5
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 35 publications
5
27
5
2
Order By: Relevance
“…It is comparable with the prevalence reported from Nigeria, 54% [20] and other two studies of China, 52.3% [12] and 56.4% [25]. However, it is higher than the prevalence reported from Abuja state in the Nigeria, which was 38.9% [22]. The differences may be attributed to the reality that only newly identified hypertensive individuals were involved in the Nigerian study.…”
Section: Discussionsupporting
confidence: 77%
“…It is comparable with the prevalence reported from Nigeria, 54% [20] and other two studies of China, 52.3% [12] and 56.4% [25]. However, it is higher than the prevalence reported from Abuja state in the Nigeria, which was 38.9% [22]. The differences may be attributed to the reality that only newly identified hypertensive individuals were involved in the Nigerian study.…”
Section: Discussionsupporting
confidence: 77%
“…During the apartheid era, the Black majority were predominantly in the lower socioeconomic stratum and have historically been marginalized with limited access to education, [7][8][9] in females (Table 2), while in South Asians living in South Africa the prevalence is higher in males compared with females (Table 4). 34 In European countries the prevalence of MetS differs little between sex (Table 1), while in Australia a large population study showed a much higher prevalence in males than females (Table 1), 15 a pattern also observed from studies in South Korea 17 and Turkey (Table 2).…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…When compared with rural Black African populations, an estimated 13.6% more women present with MetS in the urban setting, 3 which may be due to the higher prevalence of obesity associated with the urban environment. [7][8][9] Most of the studies conducted in sub-Saharan Africa on the epidemiology and etiology of MetS have occurred in South Africa, and this country, like the rest of Africa is progressing through a nutrition transition with rising levels of obesity and non-communicable diseases (NCD). 35 Therefore, the purpose of this qualitative systematic review was to describe the epidemiology of MetS across Africa and to review data from South Africa on the demographic, behavioral and physiological factors that contribute to the development of MetS as these may be applicable to other African countries.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Thus, it is of great concern that about 98% of the female patients had abdominal obesity; this gender constitutes the majority in the group of the abdominally obese patients that had a higher cluster of the components of the metabolic syndrome. The implication of this finding is that more of the female patients (than the males) now have increased risk of CVD due to inappropriate body fat distribution.…”
Section: Discussionmentioning
confidence: 99%
“…However, after reviewing all the definitions from the WHO, EGIR, and NCEP ATP III, [22][23][24] the International Diabetes Federation (IDF) came out with a new worldwide definition for the metabolic syndrome that placed abdominal obesity as central to the pathogenesis of the metabolic syndrome. 21 Although several Nigerian studies have reported on the prevalence of the metabolic syndrome and some of its components, [25][26][27][28][29] none has addressed the central role of abdominal obesity in the prevalence of the metabolic syndrome in this population. Given that several Nigerian studies have identified abdominal obesity in both adults and children in this population, [14][15][16][17][18][19][20] this study is aimed at assessing the prevalence of the components of the metabolic syndrome in type 2 diabetes mellitus (T2DM) patients using the IDF worldwide definition that was based on abdominal obesity.…”
Section: Introductionmentioning
confidence: 98%